The Chinese Communist Youth League : Juniority and Responsiveness in a Party Youth Organization. - Tsimonis, Konstantinos (China: from Revolution to Reform Ser., 2021)
In 2003, President Hu Jintao instructed Communist Youth League cadres to 'keep the Party assured and the Youth satisfied'. This laconic recognition that winning the support of Chinese youth requires a more responsive engagement with their interests and demands, provided the League with a new youth work mandate to increase its capacity for responsiveness. This original investigation uses a combination of interviews, surveys and ethnography to examine the often contradictory and self-defeating ways the League implemented this mandate locally and nationally. By doing so, it also sheds light on Xi Jinping's decision to downgrade it politically and organizationally in 2016. This book introduces a previously unexplored organization and develops 'juniority' as a conceptual tool that captures the ways generational power is institutionalized and fuels youth political apathy. For this reason, apart from China scholars, this study will be of particular interest to those working on comparative youth politics and sociology.